An Analysis of Speech Act Classification Used By The Characters In “Onward” Movie - Galuh Fitriana Sakti (Riviera Publishing, 2022)
Introduction: Film is a symbol of real life portrait. This can be a debatable choice for the subject of discourse analysis because it resembles real-life conditions. Onward film is one of the films that depicts the use of English as a dialogue and highlights speech that conveys the classification of speech acts. Purpose: The purpose of this study was to investigate the types of speech acts uttered by the main character. In addition, this study will also investigate the purpose of characters using speech acts. Methods: This study uses a qualitative research with a pragmatism approach. The author applies the pragmatism theory developed by Yule (1996) with the types of speech acts: Declaration; Representative; Instruction; Commissive and Expressive. Results: The results reveal that; 1) Five speech acts are found in the film Onward with a total of 14 dialogues; 2) there are several purposes, each of which is used by the characters, the use of statements is mostly spoken by the police because only the police have a special role in the Onward Film. Conclusion: The use of representative speech acts used by the characters is to state what the speaker believes to be true or not. Directive speech acts are used by characters to ask someone to do something by ordering, suggesting, ordering, or asking. Commissive is used by characters to commit themselves to doing something they will do later. Finally, the use of expressiveness in the film Onward is to express feelings of pain, pleasure, sadness, and pleasure.